The Influence of Leverage, Profitability, and Company Size on Audit Delay - Fitriadi, Fitriadi; Amiruddin, Amiruddin; Alam, Syamsu (SENTRALISASI, 2025)
This study aims to examine the influence of leverage, profitability, and Company Size on audit delay. The delay in delivering audit results will affect investors' perceptions in making investment decisions. This research was conducted on companies under the Lippo Group that are listed on the IDX using secondary data and analyzed using multiple linear regression analysis. The research results indicate that leverage, profitability, and company size do not affect audit delay, whereas simultaneously, leverage, profitability, and company size do affect audit delay. This research is expected to provide practical implications for management in managing the company to issue audited financial statements on time, thereby maintaining the trust of investors and other stakeholders as a manifestation of transparency and accountability. This research is also expected to provide implications for auditors in conducting the audit process to remain professional and apply the principle of caution without being burdened by the company's conditions, whether in the form of debt issues, profitability, company size, or other variables that can affect the auditor's performance.